Failure of ossification of the occipital bone in mandibuloacral dysplasia type B. Issue 10 (13th July 2016) - Haye, Damien; Dridi, Hend; Levy, Jonathan; Lambert, Véronique; Lambert, Maurice; Agha, Mohamed; Adjimi, Frédéric; Kohlhase, Jürgen; Lipsker, Dan; Verloes, Alain
Abstract : Mandibuloacral dysplasia with type B lipodystrophy is a rare autosomal recessive disease characterized by atrophic skin, lipodystrophy, and skeletal features. It is caused by mutations in ZMPSTE24, a gene encoding a zinc metalloproteinase involved in the post‐translational modification of lamin. Nine distinct pathogenic variants have been identified in 11 patients from nine unrelated families with this disorder. We report a 12‐year‐old boy with mandibuloacral dysplasia with type B lipodystrophy and a novel homozygous c.1196A>G; p.(Tyr399Cys) mutation in ZMPSTE24 . The patient had typical dermatological and skeletal features of mandibuloacral dysplasia with type B lipodystrophy, sparse hair, short stature, mild microcephaly, facial dysmorphism, and a striking failure of ossification of the interparietal region of the occipital bone, up to the position where transverse occipital suture can be observed. Newly recognized signs for mandibuloacral dysplasia with type B lipodystrophy were gaze palsy and ptosis. Delayed closure of cranial sutures and Wormian bones have been described in three patients, but an ossification failure strictly limited to the occipital bone, as seen in the present patient, appears to be unique for mandibuloacral dysplasia with type B lipodystrophy. This observation illustrates that ZMPSTE24 could play a specific role in membranous ossification in the interparietal part of the squama (Inca bone) but not in the intracartilaginous ossification of the supraoccipital. This failure of ossification in the squama appears to be a useful feature for the radiological diagnosis of mandibuloacral dysplasia with type B lipodystrophy. © 2016 Wiley Periodicals, Inc.